IMPACT OF PUBLIC JOINT STOCK COMPANIES USING THE INCOME SMOOTHING METHOD ON SHARE'S MARKET VALUE: COMPARATIVE RESEARCH OF INDUSTRIAL AND SERVICE COMPANIES LISTED ON THE PALESTINE AND ABU DHABI STOCK EXCHANGES (2020) (INTERNATIONAL JOURNAL OF ACCOUNTING AND FINANCIAL MANAGEMENT RESEARCH AND DEVELOPMENT (IJAFMRD), 2023)
The research aimed to know to what extent the public companies use income smoothing techniques and its impact on the market value of industrial and service companies listed on the Palestine and Abu Dhabi Stock Exchanges. The research also aimed to test the relationship between the type of sector the company belongs to and the practice of income smoothing. The research relied on the descriptive analytical method in conducting the research. The data used in this research was obtained from the income records of 57 companies listed on the Palestine and Abu Dhabi stock exchanges (26 companies listed on the Palestine Stock Exchange and 31 companies listed on the Abu Dhabi Stock Exchange) during the period from (2010-2019). The research used Eckel's (1981) model to classify companies into smoothing or non-smoothing for their income, and four measures of income were used: gross income, net operating income, income before tax, and net income. The data were analyzed using descriptive tests and the Statistical Package for Social Sciences (SPSS), while to test the research hypotheses, t-test and multiple regression analysis were used.The research found that some Emirati and Palestinian companies practice the income smoothing technique, as income smoothing appeared in all four measures of income in the two markets in different proportions. Further, the research found that there is a statistically significant effect of the income smoothing behavior on the market value.The research found that there are statistically significant differences between industrial and service companies in the behavior of income smoothing using different income measures.